The Influence of Good Corporate Governance, Corporate Social Responsibility, and Intellectual Capital on Financial Performance in Plantation Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2020: Pengaruh Good Corporate Governance, Corporate Social Responsibility, Dan Intellectual Capital Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Subsektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019 – 2020 - Iktiasari, Firra Mayang; Setiyono, Wisnu Panggah (Indonesian Journal of Innovation Studies, 2022)
The strategy carried out by the company must have strong competitiveness in national and international markets. One of the important goals of establishing a company is to increase the welfare of its owners or shareholders, or maximize shareholder wealth through increasing the value of the company. This study uses a quantitative method, the sample was selected by the purposive sampling method, namely 10 manufacturing companies in the plantation sub-sector, which are listed on the IDX for the 2019-2020 period. The data collection technique uses the company's annual report from the 2019-2020 period. The analytical technique used in this study is path analysis with the help of the Eviews 8 program. The results of this study indicate that Good Corporate Governance has a value of 0.04 < 0.05, Corporate Social Responsibility 0.29 < 0.05, and Intellectual Capital 0.46 < 0.05, which means the variable Good Corporate Governance , Corporate Social Responsibility, and Intellectual Capital have a very significant effect on the performance of manufacturing companies in the plantation sub-sector.